Types, Risk Factors, Clinical symptoms and Diagnostic Tests of Acute Adult Meningitis in Northern Iran During 2006-2012 - Masoumeh Bagheri-Nesami; Farhang Babamahmoodi; Attieh Nikkhah (Journal of Clinical and Diagnostic Research, 2015)
Background: Acute bacterial meningitis is a medical emergency condition that requires prompt diagnosis and treatment and otherwise associated with serious morbidity and mortality. Aim: The aim of this study was to assess types, risk factors, clinical symptoms and diagnostic tests of meningitis in hospitalized patients of Mazandaran University of medical sciences hospitals during 2006-2012. Matherials and Methods: This is a retrospective descriptive study. Following approval of the ethics committee of Mazandaran University of Medical Sciences, records of adult patients diagnosed with acute meningitis from 2006 to 2012 were extracted from Mazandaran Provincial Health Center and patients attending hospitals affiliated to Mazandaran University of Medical Sciences. Statistical analysis: Data were analyzed with SPSS-16 using descriptive statistics (frequency, mean, standard deviation, and median). Results: In this study, of the 137 patients with meningitis, 73 (53.9%) were viral, 61 (46%) bacterial, 1 (0.7%) fungal, and 2 (1.4%) unknown. The majority of risk factors in patients were head trauma, upper respiratory infection, and drug addiction. The most common clinical signs were headache, fever, nausea and vomiting, and stiff neck. Conclusion: In this study, the incidence of meningitis was much lower than any other country. It could be due to geographic variation or incomplete recording of patient's data. It is recommended to perform a longitudinal study during the coming years on patients with meningitis.